Effects of the Combination of Noise Reduction Earplugs with White Noise and Rational Emotional Therapy on Emotional States of Inpatients with Colorectal Cancer - Yifei Wang; Jiandong Fei; Yanan Zheng; Ping Li; Xiaodong Ren; Yongzhu An (Noise and Health)
Objective: The aim of the study was to explore the effects of the combination of noise reduction earplugs with white noise and rational emotional therapy on the emotional states of inpatients with colorectal cancer (CRC). Methods: The study selected 152 CRC patients who received inpatient treatment in our hospital from January 2020 to January 2022 as the research objects. According to different nursing intervention modes, these patients were divided into the observation group (OG, n = 73, conventional nursing + noise reduction earplugs with white noise + rational emotional therapy) and the control group (CG, n = 79, conventional nursing) to compare the emotional status, sleep quality, and other indicators between the two groups. Results: After 2 and 6 weeks of intervention, the severity of illness and global impression in the OG were notably lower than those in the CG. The OG had remarkably higher efficacy indexes than the CG (p < 0.05). The OG had overtly lower Montgomery-Asberg Depression Scale (MADRS) scores and Pittsburgh sleep quality index (PSQI) scores than the CG (p < 0.05). Conclusion: The combination of noise reduction earplugs with white noise and rational emotional therapy can improve the emotion and sleep states of patients, with certain positive effects, which can be used as a potential nursing plan for CRC patients.